Decellularization in Tissue Engineering and Regenerative Medicine: Evaluation, Modification, and Application Methods - Neishabouri, Afarin; Soltani Khaboushan, Alireza; Daghigh, Faezeh; Kajbafzadeh, Abdol-Mohammad; Majidi Zolbin, Masoumeh (Frontiers in Bioengineering and Biotechnology, 2022)
Reproduction of different tissues using scaffolds and materials is a major element in regenerative medicine. The regeneration of whole organs with decellularized extracellular matrix (dECM) has remained a goal despite the use of these materials for different purposes. Recently, decellularization techniques have been widely used in producing scaffolds that are appropriate for regenerating damaged organs and may be able to overcome the shortage of donor organs. Decellularized ECM offers several advantages over synthetic compounds, including the preserved natural microenvironment features. Different decellularization methods have been developed, each of which is appropriate for removing cells from specific tissues under certain conditions. A variety of methods have been advanced for evaluating the decellularization process in terms of cell removal efficiency, tissue ultrastructure preservation, toxicity, biocompatibility, biodegradability, and mechanical resistance in order to enhance the efficacy of decellularization methods. Modification techniques improve the characteristics of decellularized scaffolds, making them available for the regeneration of damaged tissues. Moreover, modification of scaffolds makes them appropriate options for drug delivery, disease modeling, and improving stem cells growth and proliferation. However, considering different challenges in the way of decellularization methods and application of decellularized scaffolds, this field is constantly developing and progressively moving forward. This review has outlined recent decellularization and sterilization strategies, evaluation tests for efficient decellularization, materials processing, application, and challenges and future outlooks of decellularization in regenerative medicine and tissue engineering.